2018
DOI: 10.3389/fneur.2018.01118
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Congenital Internal Carotid-Jugular Fistula

Abstract: A carotid-jugular fistula is a direct communication between the carotid artery and the jugular vein. Both congenital and spontaneous internal carotid-jugular fistulas are extremely rare. We describe the first case of successful endovascular treatment for a congenital internal carotid-jugular fistula. We report a 64-year-old woman who presented with a pulsatile mass swelling over the left cervical region and right hemiparesis after cough. Digital subtraction angiography confirmed the diagnosis of left high-flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Embolization of branches of the ICA is considered a risky procedure and can be complicated by embolic accidents such as blindness or ischemic stroke 12–14 . Nevertheless, many authors have reported the possibility of embolization of branches of the ICA for various indications, including skull base tumors 15–19 . However, to our knowledge, there is no report of superselective embolization of branches of the ICA in JNA; the possibility of nonselective embolization under ICA occlusion has been described in one case of JNA 20 .…”
Section: Discussionmentioning
confidence: 98%
“…Embolization of branches of the ICA is considered a risky procedure and can be complicated by embolic accidents such as blindness or ischemic stroke 12–14 . Nevertheless, many authors have reported the possibility of embolization of branches of the ICA for various indications, including skull base tumors 15–19 . However, to our knowledge, there is no report of superselective embolization of branches of the ICA in JNA; the possibility of nonselective embolization under ICA occlusion has been described in one case of JNA 20 .…”
Section: Discussionmentioning
confidence: 98%
“…[1] Congenital fistulas are extremely rare and there are few case reports in the literature. [2,3] Nowadays, iatrogenic AV-fistulas are observed more frequently in the neck region because of the increased number of catheterizations needed for central venous access or temporary hemodialysis and cardiac pacing. [4] Vascular injuries to the neck arteries necessitate a rapid correction.…”
Section: Discussionmentioning
confidence: 99%
“…Reported cases of an external carotid artery (ECA) and IJV fistula included a 15-year-old-female and a 2-year-old male who presented with a pulsatile swelling in the neck [2,20], and a 27-year-old-male with neurological manifestations besides a neck swelling [50]. A fistula between the ICA and IJV was reported in a 64-year-old female with a pulsating swelling and bruit [131]. Lagos also reported a fistula between the ICA/IJV in a 7-year-old patient who presented with status epilepticus [64].…”
Section: Congenital Arterio-venous Fistulasmentioning
confidence: 99%